Anti-Listerial Effect of Selected Essential Oils and Thymol - Kerekes, Erika-Beáta; Vidács, Anita; Török, Julianna Jenei; Gömöri, Csilla; Petkovits, Tamás; Chandrasekaran, Muthusamy; Kadaikunnan, Shine; Alharbi, Naiyf S.; Vágvölgyi, Csaba; Krisch, Judit (Acta biologica Hungarica, 2016)
The anti-listerial effect of marjoram, thyme essential oils (EOs) and thymol on Listeria monocytogenes inoculated chicken breast fllets was investigated. Before inoculation the fllets were pretreated by washing or not under running tap water. Inoculated samples were kept at 6 °C for 24 h to allow the growth of L. monocytogenes . After this, the fllets were put in marinating solutions containing salt (5%) and EOs or thymol in MIC/2 concentration established in vitro . Total germ count (TGC) and L. monocytogenes count was monitored on the meat surface and in the marinating solutions following 24 and 48 h storage at 6 °C. Thyme and thymol reduced signifcantly Listeria cell count (1–3 log CFU) in both samples. They also gave good favour to the fried meat. The doses of EOs used were optimal for antimicrobial effciency and had a pleasant favour effect. Washing was not effcient in reducing total germ count.